Robust, Easy‐Cleaning Superhydrophobic/Superoleophilic Copper Meshes for Oil/Water Separation under Harsh Conditions. Issue 11 (26th April 2019) - Pang, Bo; Liu, Huan; Liu, Peiwen; Zhang, Hua; Avramidis, Georg; Chen, Longquan; Deng, Xu; Viöl, Wolfgang; Zhang, Kai
Abstract: Facile and low‐cost methods for the fabrication of superhydrophobic and superoleophilic materials to effectively separate oil/water mixtures are of great interest and significance. Especially, those with robust surfaces for the separation under harsh conditions including corrosive solutions and hot water are still very challenging. In this paper, Cu(OH)2 nanoneedles and CuO nanoplates are controllably generated on copper meshes by simply changing the oxidization time. After hydrophobic coating with polydimethylsiloxane, the as‐prepared copper meshes not only possess superhydrophobicity with static water contact angle up to 160.2° ± 2.6° and superoleophilicity but also exhibit high resistance against peeling and abrasion cycles. The superhydrophobic/superoleophilic meshes are also utilized to separate various oil/water mixtures with a high separation efficiency up to 98.89%. Moreover, a high separation efficiency of over 97% can be maintained after at least 30 separation cycles and a slight decrease in the flux caused by oil contamination is easily recoverable after rinsing with ethanol. In addition, these meshes demonstrate high separation efficiency for separating mixtures of diesel and diverse corrosive solutions or hot water (above 97 °C). These combined advantages make the meshes promising candidates for practical applications. Abstract : Superhydrophobic/superoleophilic copper meshes are fabricated by in situ generated Cu(OH)2 nanoneedles or CuO nanoplates and subsequently hydrophobic coating with polydimethylsiloxane. The resultant superhydrophobic copper meshes not only demonstrate high resistance against peeling and abrasion but also exhibit high separation efficiency for various mixtures of oils and aqueous solutions under harsh conditions.